High throughput UHPLC-MS/MS method for the simultaneous quantification of six vitamin D metabolites: application for vitamin D determination in patients after liver or kidney transplantation. Issue 46 (11th November 2020) - Hu, Ting; Li, Han; Liu, Hongchuan; Cong, Ling; Liu, Lihong; An, Zhuoling
Abstract : Vitamin D metabolites are fat-soluble vitamins that regulate broad spectrum of physiological and pathological processes. Abstract : Vitamin D metabolites are fat-soluble vitamins that regulate broad spectrum of physiological and pathological processes. Accurate and high-throughput methods for the detection of vitamin D metabolites are essential to elucidate body functions. In this study, a sensitive and high throughput ultra-high performance liquid chromatography with tandem mass spectrometry (UHPLC-MS/MS) method was proposed for the accurate quantification of six vitamin D metabolites, including vitamin D2, vitamin D3, 25-hydroxyvitamin D2, 25-hydroxyvitamin D3, 1, 25-dihydroxyvitamin D2, and 1, 25-dihydroxyvitamin D3 . Through the optimization of chromatographic and mass spectrometric conditions, only 20 μL serum or plasma could satisfy the quantification of six vitamin D metabolites. The limit of detection (LOD) was determined to be 0.02–0.05 pg mL −1 . The validation method was carried out following the International Council for Harmonization (ICH) guidelines. All quantification performances, including linearity, accuracy, precision, extraction recovery and matrix effect, were investigated and were satisfactory for the accurate detection of vitamin D metabolites. A disease of the liver or kidney, the main organs for vitamin D metabolism, could lead to abnormal levels of vitamin D. Here, the established UHPLC-MS/MS method was further used for determination of vitamin D levels in plasma samples of patients after liver or kidney transplantation. Thirty-three liver transplant recipients (LTRs) and 63 kidney transplant recipients (KTRs) were included in this study. Vitamin D deficiency or insufficiency is common in KTRs and LTRs, with a prevalence of more than 99%.